Development of molecular detection kit for Larimichthys crocea and Larimichthys polyactis - Cho, Hyunseok; Kim, Ji-Hoon; Lee, Won Sun; Jeong, Woochang; Moon, Hyo-Bang; Hwang, Seung Yong (Biochip journal, 2014)
Large yellow croaker ( Larimichthys crocea ) and redlip yellow croaker ( L. polyactis ) are commonly consumed species in fisheries markets in East Asian countries. They have wide differences of price due to consumer preferences for L. polyactis . However, it is difficult to identify the species based on the appearance of both species from the general public. In this study, a real-time polymerase chain reaction (PCR) kit was designed to distinguish these two species. Speciescommon primer pairs were designed, and two speciesspecific probes were designed with sequences that were 2 bp different. The L. crocea target probe was modified using HEX dye, whereas the L. polyactis was modified using FAM dye. These primer pairs and probes worked in a single reaction. Based on the confirmation of a simple peak image, both species were sufficiently distinguished. The PCR kit developed in our study can be suggested as a good tool to distinguish both fish species for consumer as well as producer. In addition, the species-specific probes can be used as the biomarker, which applies to the lab-on-a-chip technology.